Effects of glosses on learning of L2 grammar and vocabulary. (January 2016) - Jung, Jookyoung
The present study examines how glossing of second language (L2) texts affects L2 learners' reading comprehension as well as their learning of L2 grammar and vocabulary. It employed a pretest, immediate posttest, and delayed posttest design with two treatment sessions. The target features were English unaccusativity and 10 pseudo-word items. Participants were 52 Korean college students learning English, who were randomly assigned to a glossed or unglossed condition. Glossing was achieved by means of providing Korean translation of each targeted item in the margin of the text. Reading comprehension was measured with 14 multiple-choice items for each text. The learning of the target features was assessed with a grammaticality judgment test and a word form and meaning recognition test. These tests were supplemented with reaction time data and binary confidence ratings in order to assess the solidity of the knowledge acquired. The results indicated that glossing significantly facilitated learning of the target constructions, while having no influence on reading comprehension scores. These results will be discussed in light of potential usefulness of glossing as a means to facilitate learning of L2 grammatical and lexical features.